Evolving economic architecture in East Asia - Masahiro Kawai (Asian Development Bank Institute (ADBI), 2007)
This paper examines how East Asia's economic architecture has been evolving over the last ten years and how it will shape itself in the future. With the progress of market-driven economic integration, East Asian economies have developed various cooperative initiatives for trade and finance, including free trade agreements (FTAs), the Chiang Mai Initiative, the Economic Review and Policy Dialogue, and the Asian Bond Markets Initiative. The paper suggests policy directions for greater regional economic cooperation. First, trade authorities are advised to consolidate multiple, overlapping FTAs into a single East Asian agreement - particularly among the East Asia Summit (EAS, or ASEAN+6) countries - to minimize negative 'noodle bowl' effects and achieve 'deep, WTO-plus' integration. Second, financial authorities are encouraged to initiate exchange rate policy coordination - starting with the adoption of a regional currency-basket arrangement based on the US dollar, euro, and Asian Currency Unit. East Asia's economic architecture will be shaped around ASEAN+3 and EAS (or ASEAN+6), with ASEAN as the hub for economic cooperation and integration.
Keywords: F02; F15; F21; F31; F33; F42; 330; Wirtschaftsintegration; Handelsregionalismus; Ostasien